KEWENANGAN NOTARIS DALAM PEMBUATAN AKTA WASIAT UNTUK ANAK PIARA DALAM HUKUM ISLAM DAN PENGANGKATAN ANAK DALAM KITAB UNDANG-UNDANG HUKUM PERDATA - Ade Kusuma (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2015)
Abstract : Notaries as the public officials have the authority by law to make an authentic deed which is one of them is testamentary deed. The implementation conception will be a legacy to adopted children in accordance with Islamic law and the Civil Codex Book which have differences. Problems, How the authority of a Notary as a public official in the testamentary deed to the foster children in Islamic Law and the adoption of Children in Civil Codex Book and Islamic Law, and How to put the position of adopted children as the receivers of testamentary which is reviewed from the terms of the Civil Codex Book, Islamic Law in protecting parts of the absolute rights of the other heirs. This legal research is a normative law research which analyzes a legal enforceability. It is implemented by examining the legal materials, such as the studies of the law principles, positive law, rules of law, and rules of legal norms. This study used two approaches in the study of law, namely: Statue Approach, Historical Approach, Conceptual Approach, and Comparative Law Approach. The results showed that the implementation conception of testamentary which is the legacy under Islamic law can be made in writing and verbally. Meanwhile according to the Civil Codex Book the form is only in writing. The equality between Civil Law and Islamic Law recognizes the children adoption however with a different purpose. Adoption which is done by someone else should be done officially in order to expect the Notary to disseminate to the public in making a testamentary through Notary’s deed and Ministry of Justice and Human Rights can improve their services in order to facilitate the Notaries in requesting the data of the testamentary list to help the Notaries in creating testamentary deed. Keywords:  Notaries, Authentic Deed, Testamentary Deed, Adopted Children